Innovative Approaches to Forest Fire Prevention: Integrating Technology and Ecological Strategies. A Comprehensive Review - Syed Shaheer Hassan; Guang Yang; Sana Tahir; Haseeb Ahmad; Muhammad Sabir; Laila Noor; Khuzin Dinislam (South-East European Forestry, 2025)
The problems associated with the advancement of technology and the environment are growing more complicated in recent years. Wildfires are one of the most important environmental challenges since they seriously endanger the world's ecosystems. There are many different types of damage done to forests, which result in both climate change and the devastation of terrestrial ecosystems. Consequently, the implementation of efficient strategies for early warning, prevention, the efficacy of ecological methods like fuel management strategies and green fire barriers in preventing wildfires and well-coordinated treatments is necessary to lessen their impact on both people and the environment. This overview examines the development of several technologies from previous years to the present with the purpose of detecting, tracking, and preventing forest fires. It draws attention to the advantages, restrictions, and potential advancements in this field of research. Because of their catastrophic effects on ecosystems and potential consequences on the climate, forest fires have become a major environmental concern. To create more potent plans for preventing and controlling wildfires, our research demonstrated the necessity for significant advancements in ecological methods, technological breakthroughs, and community involvement to strengthen wildfire preservation efforts.